O regime de responsabilidade civil em acidentes com veículos com nível 5 de automação - Monteiro, Joana Rita Estevão Sal (2022)
Artificial intelligence is an increasingly present reality in our daily lives, which inevitably highlights the fragility of the current regimes to respond to the problems raised by this technology. One of the areas where the need to clarify and adapt the legal regime has been noted is civil liability. In this study we will analyse this same regime applied to Level 5 autonomous vehicles, the highest level of automation. Since there have already been published some international and European instruments on artificial intelligence and autonomous vehicles, as well as some national legislation on this subject, we begin by analysing them. Some of the proposals presented include the strict liability of the operator, the strict liability of the producer, the fault-based liability, the grant of legal personality to artificial intelligence, the vicarious liability, the mandatory civil liability insurance and the creation of compensation funds. We then move on to an assessment of the current response of the Portuguese civil liability regime in order to reveal its flaws when applied to autonomous vehicles. With this, we are able to find the problems of the current regimes and the presented proposals, concluding with a suggestion to adapt the current regime in order for it to better apply to autonomous vehicles, ensuring the proper protection of all stakeholders.